Bioefficacy of Insect Growth Regulators Against Aedes albopictus (Diptera: Culicidea) From Sarawak, Malaysia: A Statewide Survey - Lau, Koon Weng; Chen, Chee Dhang; Lee, Han Lim; Low, Van Lun; Sofian-Azirun, Mohd (Oxford University Press, 2018)
The susceptibility status of Aedes albopictus (Skuse; Diptera: Culicidea) larvae collected from 13 districts in Sarawak state, Malaysia was evaluated against five insect growth regulators (IGRs) namely, methoprene, pyriproxyfen, diflubenzuron, cyromazine, and novaluron. Field populations of Ae. albopictus were susceptible to methoprene, pyriproxyfen, cyromazine and novaluron with resistance ratios (RRs) ranging from 0.19–0.38, 0.05–0.14, 0.50–0.95, and 0.75–1.00, respectively. Nevertheless, tolerance towards diflubenzuron (0.33–1.33) was observed in this study. In general, these IGRs exhibited promising results and can be used as alternative control agents against field populations of Ae. albopictus in Sarawak, Malaysia.